Interest rates, not the money supply: Towards a non-monetarist interpretation of the TFEU - Philipp Orphal; Florian Kern; Max Krahé (Dezernat Zukunft e.V., 2023)
In this paper, we show that the case law on the legality of bond purchases by Eurosystem central banks is partly based on the economic theory of monetarism and, in particular, on a 1981 paper by Thomas Sargent and Neil Wallace ("Some Unpleasant Monetarist Arithmetic"). However, monetarism, already controversial in the 1970s and 1980s, is now recognised as false. The assumptions on which Sargent and Wallace based their argument were already partially inaccurate at the time; today, it is generally accepted that these assumptions do not hold in reality.2 This intellectual progress should be taken into account in ongoing interpretation of the European treaties and the European legal framework. Building on this observation, in this paper we develop an updated, "non-monetarist" interpretation of Article 123 TFEU. This interpretation deviates from the standards developed in previous case law in three ways: First, the prohibition under which the European System of Central Banks may not purchase government bonds on the secondary markets under conditions which would, in practice, have an effect equivalent to that of a direct purchase of government bonds ("prohibition of transactions with equivalent effect") should be given up on. Second, the restriction that secondary market purchases must not weaken incentives (judicially speaking, the "impetus") towards "sound fiscal policy" ("prohibition on circumvention") should be replaced. Instead of this restriction, the proper limiting principle is that secondary market purchases must pursue the objective of price stability and, if possible without compromising the first objective, support the general economic policies in the European Union. Within the purposes of Article 123 TFEU, sound public finances are only a means for achieving price stability. The focus of the interpretation should therefore be the pursuit of price stability. The general economic policy goal of sound public finances is the subject of other rules. Third, and on a related point, the Federal Constitutional Court of Germany (BverfG) should no longer ground the protection of the Bundestag's budgetary right in Article 123 TFEU. The increasingly detailed measures and prohibitions built on an extensive reading of this article are detrimental to monetary policy and thus to price stability. This does not mean that the Federal Constitutional Court should give up on protecting the Bundestag's budgetary sovereignty. Instead, the protection of the Bundestag's budgetary right should be carried out under the legal benchmarks actually created for this purpose: Articles 121, 125 and 126 TFEU.
Keywords: 330